2012
DOI: 10.1029/2011gl050797
|View full text |Cite
|
Sign up to set email alerts
|

Drought, groundwater storage and stream flow decline in southwestern Australia

Abstract: In this study we examine the hydrological processes that underpin non‐stationarity in hydrological prediction. This is achieved by analysis of linkages between rainfall, groundwater storage, and runoff in Southwest Western Australia (SWWA), a region experiencing stream flow decline since the mid‐1970s. We find a close connection between rainfall and changes in catchment groundwater storage, with increases in storage in years with annual rainfall above a threshold (1050–1400 mm), and declines during low rainfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
122
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 15 publications
3
122
0
Order By: Relevance
“…Numerous studies have assessed the trends in river runoff, the factors that influence it, and the relative contributions of different environmental factors (e.g., [35,36]). In the HRB, runoff has shown a significant downward trend in recent decades [28,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have assessed the trends in river runoff, the factors that influence it, and the relative contributions of different environmental factors (e.g., [35,36]). In the HRB, runoff has shown a significant downward trend in recent decades [28,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of rain gauges indicated that precipitation has been stationary within the watershed during the study period. Non-stationarity in inflows, coupled with stationarity in precipitation, indicate changes in the runoff ratio (defined as flow production per unit precipitation), a common indicator of changing hydrological processes (Hughes et al, 2012).…”
Section: Long-term Hydrological Trends and Human Drivers Of Changementioning
confidence: 99%
“…We examine a "perceptual" flaw in many RR models and suggest a possible update to model structure. 8 J. D. Hughes and J. Vaze: Non-stationarity and catchment storage forested, and includes the main water catchment for the Perth metropolitan areas (see Hughes et al, 2012). The regolith of the area is deep ( ∼ 40 m) and is very transmissive.…”
Section: Introductionmentioning
confidence: 99%
“…Obvious changes in the relationship follow drought years 2001 and 2010. More recent analysis (Hughes et al, 2012;Kinal and Stoneman, 2012) show that permanent groundwater plays a critical role in runoff generation. Hughes et al (2012), demonstrated that runoff ratio (Q/P ) was strongly related to groundwater elevation in the catchment, particularly in the riparian zone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation